Regulation and barriers to trade in telecommunications services in the European Union - Martin Cave; Matthew Corkery (Center for Economic Studies and ifo Institute (CESifo), 2009)
Recent advances in telecommunications, particularly using fibre technologies, permit many services based on data-processing to be performed anywhere in the world. They thus become tradable and subject to the laws of comparative advantage. A good example is data-processing within large multi-national corporations, the integrated performance of which can reduce cost and add considerable value. Whereas a single market for the provision of such services has arisen in the US, the equivalent single market in the European Union is impeded by absent or imperfect regulation conducted at the national level, which fails to create a level playing field between the country's former telecommunications monopolist and foreign competitors and prevents the emergence of trade in services, at considerable potential cost to firms operating in the EU. The paper discusses how this problem can be resolved by improved regulatory practice and evaluates the prospects for institutional change, in the form of more centralised scrutiny of regulatory remedies, which would make this more achievable.
Keywords: L5; L9; 330; Mehrwertdienst; EDV-Dienstleistung; Internationaler Dienstleistungsverkehr; Außenhandelsbeschränkung; Telekommunikationspolitik; EU-Staaten